Diagnosis of the problems in vocabulary curriculum within the jurisdiction of Architectural engineering in Iraq - Rizco, Nawfal Josef (Nahrain University College of Engineering Journal, 2011)
the fact that architecture is the embodiment of a material (physical) to the direction of a certain intellectual (philosophy (become a study in architectural engineering associated with a large number of phenomena, starting from the properties of materials to the principles or fundamentals of visualperception and everything related to human thought and philosophy, and because of that the academic vocabulary curriculum for the stages of the initial, & the post graduate studies varied and in result we found a difference in the nature of the knowledge problems facing the student in the architectural engineering according to the stage and to vocabulary in terms of structuring the problem or the complexity or in the field of construction and therefore different requirements to the solutions of those problems, by type, The research diagnose the nature of some of those knowledge problems that student face and concluded that most of the curriculum vocabulary in Architectural engineering includes ill-structural problems like( Decision Making Problem), (Diagnosis-solution problems),( Case analysis problems), in addition to ( Design problems) and in result their solutions based adapters between groups of parameters and standards which require from the problem solver whether student or professor having a knowledge of multiple fields before they begin draftingsolutions, and the key solutions to these ill-structural problems achieved by reconstruct the space problem in order to simplified the problem components .